Transformer Fault Early Warning System Model Using GSM Network - M. A. M. Azmi; Z. Nawawi; M. I. Jambak; M. A. B Sidik; Y. Z. Arief; Z. Adzis; N. A. Muhamad (IAES Indonesia Section, 2015)
This paper presents the design and implementation of amobile embedded system using an Arduino microprocessor to monitorand record key operational indicators of a distribution transformer,such as transformer oil level, temperature and vibration of adistribution transformer in a substation. If there is any abnormalityor an emergency situation, the system sends SMS (Short MessageService) messages to designated mobile telephones containinginformation about the abnormality of the mentioned parameters.Providing early warning of the abnormality of the distributiontransformer can be accomplished by shutting down the entire unitwith the aid on-line monitoring system integrates with Global ServiceMobile (GSM) Modem. Furthermore, the design generally consiststand-alone single chip microcontroller, modem and sensor packageslocated on distribution transformer site. In general, the design isdeveloped for the user to easily recognize the distribution transformerthat is suffered by any high vibration and rise in temperatures andlocated in remote or suburban area which is rarely and hard to reachfor manual monitoring. The ultimate objective is to monitor thetransformer oil level and temperature of 24 hours, 7 days a weekcontinuously besides the current and voltage parameter whichincluded in basis monitoring system